Complementary Strategy of Maternal Immunization with RSVpreF Vaccine and Monoclonal Antibodies for the Prevention of Respiratory Syncytial Virus Among Italian Infants: A Cost-Effectiveness Assessment - Barbara Polistena; Fabio Midulla; Giovanni Sotgiu; Daniela d’Angela; Roberto Di Virgilio; Federico Spandonaro (Infectious Diseases and Therapy)
Abstract Introduction Respiratory Syncytial Virus (RSV) is a leading cause of severe lower respiratory tract infections and is one of the primary causes of hospitalization in high income countries and death among children aged ≤ 1 year in lower income countries where the healthcare systems not always have the resources to provide appropriate intensive care to all infants with severe RSV infection. On the basis of the results of a large programme of clinical trials, the European Medicine Agency has recently approved a Bivalent Stabilized Prefusion F Subunit Vaccine (RSVpreFV) for maternal immunization, with a year-round administration between 24–36 weeks of gestation. The objective of the study is providing an estimation of the efficiency of complementary strategy RSVpreF and monoclonal antibodies for the prevention of RSV among Italian infants. Methods Using a model (with a cohort framework and a Markov-type process) specifically adapted to the Italian context, the study provided cost-effectiveness and cost-utility assessment of prevention strategies adding the maternal vaccination to the existing immunization opportunities with palivizumab or nirsevimab administered to high risk and unprotected infants. Results The complementary strategy RSVpreFV plus palivizumab demonstrates significative health benefits versus palivizumab alone: it would reduce annual hospitalizations by 4097 cases (−25.8%), Emergency Department (ED) admissions not followed by hospitalization by 534 (−18.8%), with 25 years of life recovered, and an increase of 90 Quality Adjusted Life Years (QALYs). The strategy results cost-saving: the complementary strategy saves € 6.0 mil and € 8.4 mil per year in the NHS and in the Societal perspective, respectively; the complementary strategies of maternal vaccination plus nirsevimab also prove to have significant benefits versus the monoclonal antibody alone, providing a decrease equal to 941 annual hospitalizations (−9.0%), 6 years of life recovered, and an increase of 20 QALYs. The strategy saves € 2.6 mil and € 3.1 mil per year in the NHS and in the Societal perspective, respectively. Conclusions RSV is a leading cause of severe lower respiratory tract infections and is one of the primary causes of hospitalization in high income countries and death among children aged ≤ 1 year in lower income; bivalent Stabilized Prefusion F Subunit Vaccine (RSVpreFV) for maternal immunization proves to be effective in preventing RSV infections, avoiding severe disease. The modelling exercise shows that the complementary strategy of maternal vaccination with palivizumab or nirsevimab are both dominant (better health outcomes with lower costs) on monoclonal antibodies alone; the sensitivity analysis confirms that the complementary strategies in most of the simulation remain dominant or cost-effective adopting a low threshold for the willingness to pay; finally the complementary strategies are also sustainable, owing to a limited impact on the current national budget for vaccines.